Pengaruh Rekrutmen dan Kompensasi Terhadap Kinerja Karyawan pada Perusahaan Umum DAMRI Cabang Lampung - Eka Travilta Oktaria; Muhamad Irvan; Hairudin Hairudin (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2022)
This study aims to determine how much influence recruitment and compensation have on employee performance. The method used in this study is a quantitative method. The sample studied amounted to 66 respondents consisting of staff and employees of the General Company Damri Branch Lampung. with the method of validity test, reliability test, classical assumption test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, T test (partial test), F test (simultaneous test) and coefficient of determination test. what the author can make is as follows: the results obtained from Fcount are 24,716. While the value of Ftable is 3.14, which means that Recruitment (X1) and Compensation (X2) have a significant influence on employee performance.